Finance and Development, December 2014. (Finance and Development; Finance and Development, 2014)
This chapter emphasizes the importance of health policy and its implementation and connection to economic growth. The chapter also offers a different view of progress in the provision of better health facilities. The study looks at today's health systems-the amalgam of people, practices, rules, and institutions that serve the health needs of a population-and at the economics behind them. The role good health plays in individuals' and households' ability to rise and remain above the poverty line is stressed. Several health reports are presented.